Development of a high-throughput multi-residue method for analysis of common pesticides in aquatic environments by automated online solid phase extraction coupled with LC-MS/MS. Issue 28 (24th June 2021) - Wang, Tielong; Zhong, Mengmeng; Lu, Meiling; Huang, Jun; Blaney, Lee; Yu, Gang
Abstract : A reliable method based on fully automated online solid phase extraction coupled with LC-MS/MS was developed for the high throughput analysis of 111 common pesticides or metabolites in three aquatic matrices. Abstract : The present work describes the development of a fully automated method based on online solid phase extraction (SPE)-liquid chromatography-tandem mass spectrometry (LC-MS/MS) for the simultaneous analysis of multiple classes of pesticides or metabolites in drinking water (DW), surface water (SW), and wastewater effluents (WWEs). The target list covers 111 pesticides or metabolites of various properties and families. LC-MS/MS and online SPE parameters were optimized with regard to the sorbent type, mobile phase composition, wash volume, and flowrate as well as the injection volume. The method showed good linearity in two concentration ranges with 97% and 94% of the coefficients ( R 2 ) being higher than 0.99 in the low concentration range (0.1–100 ng L −1 ) and high concentration range (100–2500 ng L −1 ), respectively. High sensitivity was observed with method quantification limits (MQLs) of 0.03–5.3 ng L −1, 0.06–17 ng L −1, and 0.08–21 ng L −1, for DW, SW, and WWE, respectively. The recoveries showed an accuracy of 94%, 91%, and 91% in the range of 70–130% for three matrices with satisfactory precision. The overall analysis time per sample was 30 min with minimum pretreatment. To the best of our knowledge, for the first time, 64 pesticides were identified by the high throughput online SPE-based method. The optimized method was used for WWE sample analysis, and 49 pesticides were detected in 12 WWE samples from an economically active city in China. Five pesticides were detected in all the samples, i.e. paclobutrazol, atrazine, diuron, acetamiprid, and triadimenol, and the highest median concentration was observed for carbendazim (324 ng L −1 ). The advantages of the proposed method over offline ones make it have broad prospects in high throughput and reliable analysis of pesticides in aquatic environments.